ANALISIS KINERJA MESIN LASER CUTTING TRULASER 1030 PADA PRODUKSI KENDARAAN KHUSUS MENGGUNAKAN METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) - Fariz Wisda Nugraha; Sendie Yuliarto Margen; Rifky Ismail; Muhammad Farel; Yusuf Subagyo; Hartanto Prawibowo; Rizal Mustofa (Politeknik Negeri Semarang, 2025)
The manufacturing industry is continuously challenged to improve production efficiency and quality. Production machinery plays a crucial role in supporting smooth manufacturing processes, especially in the fabrication of special vehicle components. One such machine is the TruLaser 1030, a 2D laser cutting machine manufactured by TRUMPF, which is used for processing body and accessory parts in special vehicles. This study aims to evaluate the performance of the TruLaser 1030 machine using the Overall Equipment Effectiveness (OEE) method, as well as to identify damaged machine components and maintenance requirements. The Total Productive Maintenance (TPM) approach is applied to enhance equipment effectiveness, prevent breakdowns, and ensure product quality and workplace safety. The OEE methodology involves three main parameters: Availability, Performance Rate, and Quality Rate. The results show the machine’s availability at 94%, performance rate at %, and quality rate at 97.1%. These findings suggest that the TruLaser 1030 machine operates at a relatively optimal level; however, regular evaluations of work systems and maintenance programs are necessary to maintain stable performance and continuously improve productivity.